2020
DOI: 10.3390/catal10030344
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Meropenem by Heterogeneous Photocatalysis Using TiO2/Fiberglass Substrates

Abstract: Meropenem (MER), a carbapenem, is considered a last-resort antibiotic. Its presence in water bodies, together with other antibiotics, has brought about environmental problems related to the destruction of natural microorganisms and the development of antibiotic-resistant bacteria. Herein, the degradation of MER by heterogeneous photocatalysis using TiO2 immobilized on fiberglass substrates is reported. Morphological characterization of the substrates was performed by Scanning Electron Microscopy (SEM). Three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…73,76 Another research study found that lignocellulosic bioadsorbents derived from sawdust waste exhibited a 92% removal efficiency for meropenem, which increased to 96% after post-treatment (Figure 7, Table 4). 77 Further research is needed due to the importance of meropenem as the last line of defense for treating severe bacterial infections.…”
Section: Meropenemmentioning
confidence: 99%
“…73,76 Another research study found that lignocellulosic bioadsorbents derived from sawdust waste exhibited a 92% removal efficiency for meropenem, which increased to 96% after post-treatment (Figure 7, Table 4). 77 Further research is needed due to the importance of meropenem as the last line of defense for treating severe bacterial infections.…”
Section: Meropenemmentioning
confidence: 99%
“…Another attractive type of process is based on the photocatalytic generation of •OH with ultraviolet and visible radiation. In this sense, a great variety of solid semiconductors (suspended or supported) were proposed for water and wastewater treatment by heterogeneous photocatalysis [31][32][33][34][35][36]. To evaluate the efficiency of AOPs, the decrease in the concentration of a target pollutant, the chemical oxygen demand (COD) and the total organic carbon (TOC) are generally measured.…”
Section: Introductionmentioning
confidence: 99%